A new clade of Dickeya spp. plays a major role in potato blackleg outbreaks in North Finland - Degefu, Yeshitila; Potrykus, Marta; Golanowska, Malgorzata; Virtanen, Elina; Lojkowska, Ewa (Annals of Applied Biology)
2013